2009
DOI: 10.1007/s11738-009-0420-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of calcium on the antioxidant systems in the halophyte Cakile maritima under salt stress

Abstract: The purpose of the current investigation was to study the effect of Ca 2? (0, 3.5 and 20 mM concentrations) on the antioxidant systems in the halophyte Cakile maritima under NaCl stress (0, 100, 200 and 400 mM NaCl). Plants treated with both moderate calcium (3.5 mM) and salt levels (100 mM) showed the maximum growth, and the addition of 20 mM calcium to the nutrient media did not significantly reduce the growth under the moderate salt treatment. The absence of calcium associated with high salt concentration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 60 publications
7
12
0
Order By: Relevance
“…For glycophytes, the importance of Ca 2þ in mitigating the effects of salinity has long been known (see Greenway and Munns, 1980) and for some halophytes there is evidence that additional Ca 2þ and Mg 2þ can counteract detrimental effects of NaCl alone (e.g. Nedjimi et al, 2009;Ben Amor et al, 2010;Grigore et al, 2012;English and Colmer, 2013). The results of such experiments support the view that seawater (or an ion composition that resembles that of the habitat) should be the basis of any hydroponic culture of halophytes.…”
Section: Summing Up On the Topic Of Cytoplasmic Ion Concentrationsmentioning
confidence: 72%
“…For glycophytes, the importance of Ca 2þ in mitigating the effects of salinity has long been known (see Greenway and Munns, 1980) and for some halophytes there is evidence that additional Ca 2þ and Mg 2þ can counteract detrimental effects of NaCl alone (e.g. Nedjimi et al, 2009;Ben Amor et al, 2010;Grigore et al, 2012;English and Colmer, 2013). The results of such experiments support the view that seawater (or an ion composition that resembles that of the habitat) should be the basis of any hydroponic culture of halophytes.…”
Section: Summing Up On the Topic Of Cytoplasmic Ion Concentrationsmentioning
confidence: 72%
“…Despite the lower levels of calcium present in the root zone soil at site C, the roots of this plant contain a higher level of this element. This may correspond to the significance of calcium in adaptation of plants to high salinity (Ben Amor et al 2010 ), since this element plays an important role in the functioning of cell membranes, affecting their permeability and selectivity, and is involved in numerous metabolic processes in plant cells (Ben Amor et al 2010 ). As in our research work, Yang et al ( 2016 ) had also observed high concentrations of K + , Ca 2+ , Na + , and Mg 2+ in sunflower roots grown in a saline environment.…”
Section: Discussionmentioning
confidence: 96%
“…The authors justified the presence of high Ca 2+ content in roots and its importance in preventing cellular damage (Yang et al 2016 ). There are some reports considering the connection between high Ca 2+ levels and an increase in antioxidant enzyme activity as well as on the reduction of lipid peroxidation in cell membranes (Ben Amor et al 2010 ) under saline conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Electrolyte leakage has been thought to be another method of oxidative stress assessment [4]. Treatment of seedlings with salt stress resulted in a marked increase in electrolyte leakage.…”
Section: Discussionmentioning
confidence: 99%